2023
DOI: 10.3390/molecules28155803
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Enzymatic Synthesis and Biological Assessment of p-Coumarate Fatty Esters: New Antifungal Agents for Potential Plant Protection

Cyrian Thaeder,
Juliette Stanek,
Julien Couvreur
et al.

Abstract: One trend in agriculture is the replacement of classical pesticides with more ecofriendly solutions, such as elicitation, which is a promising approach consisting of stimulating the natural immune system of a plant to improve its resistance to pathogens. In this fashion, a library of p-coumaric-based compounds were synthesized in accordance with as many principles of green chemistry as possible. Then, these molecules were tested for (1) the direct inhibition of mycelium growth of two pathogens, Botrytis cinere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This compound showed no activity against other tested microbes and insignificant activity with C. albicans. From previous studies, compound C showed inhibition of mycelium growth of two pathogens, Botrytis cinerea and Sclerotinia sclerotiorum [50]. Dodecyl-p-coumarate also displayed high leishmanicidal activity (16.34 ± 0.49, Leishmania braziliensis amastigotes, EC 50 µg/mL), likely due to their relatively high lipophilicity and antiplasmodial activity (81.19 ± 8.54 Plasmodium falciparum, EC 50 µg/mL) [51].…”
Section: Anti-bacterial Anti-fungal and Cytotoxicity Studies Of A Afr...mentioning
confidence: 91%
“…This compound showed no activity against other tested microbes and insignificant activity with C. albicans. From previous studies, compound C showed inhibition of mycelium growth of two pathogens, Botrytis cinerea and Sclerotinia sclerotiorum [50]. Dodecyl-p-coumarate also displayed high leishmanicidal activity (16.34 ± 0.49, Leishmania braziliensis amastigotes, EC 50 µg/mL), likely due to their relatively high lipophilicity and antiplasmodial activity (81.19 ± 8.54 Plasmodium falciparum, EC 50 µg/mL) [51].…”
Section: Anti-bacterial Anti-fungal and Cytotoxicity Studies Of A Afr...mentioning
confidence: 91%